Pregnancy Predictors after Intrauterine Insemination in Cases of Unexplained Infertility: A Prospective Study - Ganguly, Ishita; Singh, Aparna; Bhandari, Shilpa; Agrawal, Pallavi; Gupta, Nitika (International Journal of Reproductive Medicine, 2016)
Introduction. Aim of the study was to find the effect of various prognostic factors in cases of unexplained infertility undergoing controlled ovarian stimulation (COS) with intrauterine insemination (IUI). Methods. 146 cases of unexplained infertility were included. A maximum of 3 cycles of IUI were done with clomiphene citrate/HMG. Ovulation trigger was given when the largest follicle diameter was >18 mm, and IUI was planned 36 hours later. Luteal phase support was given for 15 days, urine pregnancy test was done on day 15, ultrasonography was done at 7 weeks, and pregnancy was followed up till delivery. Results. A total of 146 couples have undergone 239 cycles of IUI out of which 27 had UPT positive after 15 days. 14.8% had 1st-trimester abortion while 3.7% were ectopic. 86.3% were singleton pregnancies and 13.6% were twins. CPR was 11.29% per cycle and 18.4% per couple; LBR was 9.2% per cycle. Apart from duration of stimulation (p=0.037) and number of treatment cycles (p=0.045), no other factors had significant prognostic value. Conclusion. For unexplained infertility, IUI can be done to provide patients with the time that they need before moving on to IVF while providing a respectable chance of pregnancy.